Implementation of Problem-Based Learning to Improve Collaboration Skills in Grade 4 Elementary School Students - Mandalika, Wayan Pudma Febby; Srihastuti, Woro; Syahrizal, Irvan; Marwan, Marwan (Mimbar Sekolah Dasar, 2024)
The learning model used by educators only transmits knowledge and does not provide opportunities for students to interact, causing them to lose time to develop their experience in the collaborative learning process. This research aims to improve collaboration skills by implementing a problem-based learning model in grade IV elementary school. The research method used is Classroom Action Research (CAR) using the Kemmis McTaggart model. The results of the research are 1) how to improve collaboration skills with a problem-based learning model using stages; a) Provide orientation regarding problems; b) Organize students; c) Assist with investigations; d) present work results; e) Analyze and apply problem-solving processes. 2) Obstacles in improving collaboration skills with learning models are; a) Students are hampered in finding problems; b) the teacher is constrained in encouraging students to investigate learning tasks related to the problem. Efforts made to overcome this problem are by presenting the problem in the form of news, videos, and photos that illustrate the problem. Students are encouraged to investigate solutions by presenting more references on how to solve the problem accompanied by news, videos, and photos of related solutions.